S234. DEPRESSION AND SEXUAL FUNCTIONING: TWO NEGLECTED AND PREVALENT DOMAINS IN PEOPLE WITH SCHIZOPHRENIA. (18th May 2020) - Lapa, Clara; Martins, Dayane; Julia Brito, Maria; Reckziegel, Ramiro; Hasse-Sousa, Mathias; Czepielewski, Leticia; Gama, Clarissa
Abstract: Background: Sexual function is highly neglected in individuals with schizophrenia (SZ). Clinicians usually underestimate the rates of sexual dysfunctions in these patients, and this group does not spontaneously complain about it. Sexual dysfunction in this population could reach up to 80% and its known to affect all domains of sexual function. Moreover, it may be linked to stigma and discrimination factors. Medication side effects on sexuality concern more than any other side effects, and it is known to be a major cause of poor quality of life and non-adherence to medication. Furthermore, the relationship between sexual dysfunction and other psychiatric symptoms in SZ is still unclear. Our aim was to describe the sexual dysfunction in chronic patients with SZ and its relation to negative, positive and depressive symptoms. Methods: A convenience and exploratory sample of 57 patients (age 43.75±10.38, 69% men, 86, 2% single) were recruited from an university outpatient schizophrenia clinic, in Porto Alegre – Brazil. Participants were assessed using Arizona Sexual Experience Scale (ASEX), Medication Adherence Rating Scale (MARS), Positive and Negative Syndrome Scale (PANSS), Calgary Depression Inventory and demographic information. Sexual dysfunction was considered following the ASEX scoring criteria. Results: Sexual dysfunction was present in 51, 8% of the patients, assessed by ASEX. Women showed increased sexual dysfunction than men (χ2=22, 727, p < .001). There were no differences between patients that reported sexual dysfunction and the ones who did not regarding age, duration of illness and medication adherence assessed by MARS (p > .05). Additionally, there were no differences between groups on positive and negative symptoms assessed by PANSS. Interestingly, patients with sexual dysfunction had increased depressive symptoms compared to patients with a good perceived sexual function (t(54) = -3.326, p = .002). Calgary total scores were positively correlated with ASEX total scores (r = .369, p = .005). Nevertheless, we did not find significant correlations between ASEX total scores and other scales. Scores found on MARS (8.07±1.5) suggest that this sample is highly adherent to prescribed treatment. Discussion: This is an exploratory and preliminary study that shows and reinforces the idea that sexual dysfunction is importantly prevalent and remains as a neglected issue in individuals with schizophrenia, as are the depressive symptoms. We showed that there is an association between these two domains, which might indicate a need for change of perspective for the pharmacological and psychosocial approaches currently used. In addition to the dopaminergic blockage by antipsychotics that lead to reduction in positive symptoms, we believe there is a need to look for depression symptoms to access, prevent and treat sexual dysfunction. Inattention to this event may result in abrupt treatment discontinuation and relapse. Curiously, the fact that we did not find any correlations between sexual evaluations and PANSS scores would suggest that sexual dysfunction in chronic patients could differ from others stages of the disease. The size of our sample and the fact that we did not access hormones and prolactin levels are important limitations of this study. However this is an exploratory study that provided clues on the subject, allowing to address further investigation taking into account the limitations.